Phân lập và khảo sát hoạt tính sinh học của các ditecpen-gamma-lacton từ lá xuyên tâm liên (Andrographis paniculata Nees). - Đậu, Nguyễn Văn; Hiếu, Lê Văn (Vietnam Journal of Chemistry, 2014)
By means of column chromatography four diterpenic -lactones were isolated from the leaves of Andrographis paniculata Nees (family Acanthaceae). Their chemical structures were elucidated by means of the modern physical methods (IR, MS and NMR) and identified as andrographolide (DM6) and neoandrographolide (DM7), and a mixture (DM4) consisting of 14-deoxyandrographolide (DA) vµ14-deoxy-11,12-didehidroandrographolide (DDA). The preliminary examination of biological activities reveals that both compounds, an®rographolide vµneoandrographolide inhibit slightly only the strain Pseudomonas aeruginosa. Besides, andrographolide exhibits the ability to inhibit considerably the growth of Hep-2.